Preparation method of high-valence element modified lithium iron phosphate
By introducing high-priced elements and organic lithium salts into lithium iron phosphate materials, combined with calcination method and doping coating technology, the problem of limited electrochemical performance of lithium iron phosphate materials is solved, and its capacity, cycle time and rate performance are significantly improved.
Patent Information
- Application Number
- CN202411947506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-22
AI Technical Summary
Lithium iron phosphate (LFP) materials have limited electrochemical properties due to their low electronic conductivity and lithium ion mobility, making it difficult to maintain excellent performance during long cycles.
Through the calcination method, high-priced elements are introduced as additives, combined with organic lithium salt and eutectic lithium salt, to achieve modification of doping and coating, and a lithium iron phosphate material with a lithium-containing ionic conductor coating layer is generated.
The capacity, circulation time and rate performance of lithium iron phosphate material are improved, the coordinated stability of the material body phase and surface structure is achieved, and the transmission capacity and circulation stability of lithium ions are enhanced.
Smart Images

Figure CN119858902A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of electrochemical energy storage materials, and in particular to a method for preparing high-valent element-modified lithium iron phosphate. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP) has become one of the most successful lithium-ion battery cathode materials in commercial applications due to its advantages of low cost, high safety, environmental friendliness, stable crystal structure, and stable operating voltage. However, LFP's electrochemical performance is severely limited due to its low electronic conductivity and lithium ion mobility. Therefore, improving the defects of the material itself and improving its reversible capacity and rate performance have become topics of common concern in academia and industry.
[0003] In the modification of lithium iron phosphate, it is more common to carbon-coat the material, which can significantly improve the electronic conductivity of the material. However, it is often difficult to achieve a relatively ideal effect by relying on a single modification method. For example, patent CN114335481A discloses a lithium iron phosphate with a conductive and ion-conducting double layer in-situ coating, and the preparation method thereof includes: mixing a fast ion conductor coating source compound, a first lithium source compound, a chelating agent and water to form a colloidal solution, and the fast ion conductor coating source compound does not contain lithium elements; mixing the lithium iron phosphate matrix material with the colloidal solution and then performing a hydrothermal synthesis reaction to obtain a fast ion conductor coated lithium iron phosphate precursor, and the lithium iron phosphate matrix material includes a second lithium source compound, a phosphorus source compound and an iron source compound; reacting the fast ion conductor coated lithium iron phosphate precursor with a carbon source coating to obtain a conductive and ion-conducting double layer in-situ coated lithium iron phosphate. The double-layer coated coating layers described in the above scheme are difficult to be tightly combined, which greatly reduces the structural stability of the material, thereby reducing its cycle stability.
[0004] In addition, it is difficult to improve the performance of lithium iron phosphate in a long cycle by coating alone. Therefore, it is urgent to find a more efficient composite method to improve the electrochemical performance of lithium iron phosphate cathode materials. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a method for preparing high-valent element-modified lithium iron phosphate, which mainly realizes high-valent element-modified lithium iron phosphate by combining doping and coating simultaneously through a calcination method. The high-valent element-modified lithium iron phosphate positive electrode material prepared by the method provided by the present invention has the characteristics of high capacity, long cycle time, good rate capability, etc.
[0006] In one aspect, the present invention provides a method for preparing high-valent element-modified lithium iron phosphate, comprising the following steps:
[0007] S1: mixing iron phosphate, lithium source, dispersant, additive and solvent to obtain slurry Y;
[0008] S2: grinding the slurry Y and spray drying it;
[0009] S3: sintering and crushing the powder collected after spray drying in step S2;
[0010] S4: Pulse sintering the powder collected after crushing in step S3 to obtain a LiFePO4 material modified with a high-valent element;
[0011] Wherein, the lithium source includes organic lithium salt and eutectic lithium salt; the additive includes organic matter of high-valent elements and inorganic matter of high-valent elements.
[0012] In the present invention, high-valent elements are introduced as additives during the preparation process. Due to their unique properties, the primary particles can be adjusted to form a relatively uniform orientation microstructure and eliminate the localized Li + The high-valent element reacts with lithium to form a lithium-containing ion conductor coating, which promotes the + It can also play a role in lithium supplementation during the cycle, prevent the electrolyte from penetrating into the high-valent element-modified lithium iron phosphate material, inhibit the interface side reaction, and achieve the coordinated stability of the bulk and surface structure of the high-valent element-modified lithium iron phosphate material; the combination of organic lithium salt and eutectic salt can not only avoid sintering at a high temperature, but also have good fluidity in the molten state, and can fully contact with iron phosphate. At the same time, the organic lithium salt of the present invention has rich functional groups, which can simultaneously realize the reduction of the iron valence state and the carbon layer coating.
[0013] In the present invention, the above step S1 may further include at least one of the following technical features:
[0014] According to an embodiment of the present invention, the lithium source consists of an organic lithium salt and a eutectic lithium salt.
[0015] According to an embodiment of the present invention, the organic lithium salt is selected from at least one of 8-hydroxyquinoline-lithium (CAS No.: 850918-68-2), dilithium carbamoyl phosphate (CAS No.: 1866-68-8), lithium 2-thioglycolate (CAS No.: 22535-44-0), lithium citrate (CAS No.: 919-16-4), and 4,5-dicyano-2-(trifluoromethyl)imidazole lithium (CAS No.: 761441-54-7).
[0016] In the present invention, the organic lithium salt not only acts as a lithium source, but also acts as a reducing agent and carbon source to a certain extent during sintering because the organic lithium salt contains more functional groups.
[0017] According to an embodiment of the present invention, the eutectic lithium salt is selected from at least one of 0.3LiOH-0.2LiNO3, 0.38LiOH-0.62LiNO3, 0.37LiOH-0.63LiCl, 0.74LiOH-0.26Li2CO3, 0.71LiNO3-0.29LiCl, and 0.55LiI-0.45LiOH.
[0018] In the present invention, eutectic lithium salt refers to a crystalline material formed by two or more different molecules in a fixed stoichiometric ratio through non-ionic bonds and non-covalent bonds; taking 0.38LiOH-0.62LiNO3 as an example, it refers to a composition of LiOH and LiNO3 with a molar ratio of 0.38:0.62, and other similar expressions are the same.
[0019] According to an embodiment of the present invention, the molar ratio of the organic lithium salt to the eutectic lithium salt is 2-5:1. The molar ratio of the organic lithium salt to the eutectic lithium salt provided by the present invention can be a value in the interval composed of any two values in the above interval, such as 2-3.5:1, or 3.5-5:1, and so on. Exemplarily, the molar ratio of the organic lithium salt to the eutectic lithium salt is one of 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1 or any ratio that satisfies the above range.
[0020] In the present invention, the lithium source is composed of an organic lithium salt and a eutectic lithium salt. If only an organic lithium salt is used, the preparation process requires sintering at a relatively high temperature, and the organic lithium salt has poor fluidity in a molten state and is not in sufficient contact with iron phosphate, which affects the crystallinity of the prepared lithium iron phosphate and results in unsatisfactory electrochemical performance. If only a eutectic lithium salt is used, the absence of a reducing agent and carbon coating makes it difficult for the prepared lithium iron phosphate to exert its physical and chemical properties.
[0021] According to an embodiment of the present invention, the dispersant is selected from at least one of polyethylene glycol (PEG), polyvinyl alcohol (PVA), polyacrylamide (PAM) and oxalic acid.
[0022] According to an embodiment of the present invention, the dispersant is 1.5%-1.6% of the mass of the iron phosphate. Exemplarily, the dispersant is one of 1.5%, 1.51%, 1.52%, 1.53%, 1.54%, 1.55%, 1.56%, 1.57%, 1.58%, 1.59%, 1.6% of the mass of the iron phosphate or any value satisfying the above range.
[0023] According to an embodiment of the present invention, the molar ratio of the additive to Fe is 0.01-0.02: 1. Exemplarily, the molar ratio of the additive to Fe is 0.01: 1, 0.011: 1, 0.012: 1, 0.013: 1, 0.014: 1, 0.015: 1, 0.016: 1, 0.017: 1, 0.018: 1, 0.019: 1, 0.02: 1 or any ratio satisfying the above range.
[0024] In the present invention, the amount of the additive affects the thickness of the coating layer. If the coating layer is too thick or too thin, the capacity of the prepared high-valent element modified lithium iron phosphate material will be reduced, the initial coulombic efficiency will be reduced, and the cycle stability of the high-valent element modified lithium iron phosphate material will be affected.
[0025] According to an embodiment of the present invention, the additive is composed of organic matter of high-valent elements and inorganic matter of high-valent elements.
[0026] According to an embodiment of the present invention, the high-valent element exists in a form selected from Ta 5+ , Nb 5+ 、Mo 6+ , W 6+ At least one of .
[0027] According to an embodiment of the present invention, the organic matter of the high-valent element is selected from at least one of tantalum ethoxide (CAS No.: 6074-84-6), niobium ethoxide (CAS No.: 3236-82-6), molybdenum hexacarbonyl (CAS No.: 13939-06-5), and tungsten isopropoxide (CAS No.: 52321-90-1).
[0028] According to an embodiment of the present invention, the inorganic substance of the high-valent element is selected from at least one of tantalum fluoride, niobium pentoxide, ammonium molybdate, and tungsten boride.
[0029] In the present invention, when calculating the molar ratio of the additive to Fe, the molar amount of the additive is: the sum of the molar amount of the high-valent element in the organic matter of the high-valent element and the molar amount of the high-valent element in the inorganic matter of the high-valent element. Taking tantalum ethoxide and tantalum fluoride as examples, it refers to: the sum of the molar amount of the tantalum element in tantalum ethoxide and the molar amount of the tantalum element in tantalum fluoride.
[0030] According to an embodiment of the present invention, the molar ratio of the organic matter of the high-valent element to the inorganic matter of the high-valent element is 5-7: 1. Exemplarily, the molar ratio of the organic matter of the high-valent element to the inorganic matter of the high-valent element is 5: 1, 6: 1, 7: 1 or any ratio satisfying the above range.
[0031] In the present invention, the additive is composed of organic matter of high-valent elements and inorganic matter of high-valent elements. Organic matter of high-valent elements, such as tantalum ethoxide, niobium ethoxide, molybdenum hexacarbonyl, and tungsten isopropoxide, can undergo hydrolysis reaction with moisture in the air, promote the uniform formation of nano-scale coating layer, stabilize the surface of the prepared lithium iron phosphate positive electrode material, and increase the ion migration speed. Inorganic matter of high-valent elements, such as tantalum fluoride, niobium pentoxide, ammonium molybdate, and tungsten boride, can increase the specific capacity of the battery. If only one of them is used, for example, only inorganic matter of high-valent elements is used, the effect of uniform formation of the coating layer cannot be achieved; if only organic matter of high-valent elements is used, the spatial structure will be relatively unstable after sintering, affecting the internal resistance of the prepared lithium iron phosphate material and reducing the capacity.
[0032] According to an embodiment of the present invention, the solvent is water.
[0033] According to an embodiment of the present invention, the solid content of the slurry Y is 30%-32%. Exemplarily, the solid content of the slurry Y is one of 30%, 31%, 32% or any value within the above range.
[0034] According to an embodiment of the present invention, the molar ratio of Li:Fe in the slurry Y is 1:1.01-1.03. Exemplarily, the molar ratio of Li:Fe in the slurry Y is one of 1:1.01, 1:1.02, 1:1.03 or any ratio within the above range.
[0035] In the present invention, the above step S2 may further include at least one of the following technical features:
[0036] According to an embodiment of the present invention, the slurry Y is ground to a D50 of 0.3 μm-0.35 μm, and then spray-dried. Exemplarily, the slurry Y is ground to a D50 of 0.3 μm, 0.31 μm, 0.32 μm, 0.33 μm, 0.34 μm, 0.35 μm or any value within the above range.
[0037] In the present invention, the above step S3 may further include at least one of the following technical features:
[0038] According to an embodiment of the present invention, the sintering process is performed under a protective atmosphere.
[0039] According to an embodiment of the present invention, the sintering process is performed in a nitrogen atmosphere or an argon atmosphere.
[0040] According to an embodiment of the present invention, the temperature of the sintering treatment is 400° C.-500° C. Exemplarily, the temperature of the sintering treatment is one of 400° C., 410° C., 420° C., 430° C., 440° C., 450° C., 460° C., 470° C., 480° C., 490° C., 500° C. or any value within the above range.
[0041] According to an embodiment of the present invention, the sintering time is 4 hours to 6 hours. Exemplarily, the sintering time is one of 4 hours, 4.5 hours, 5 hours, 5.5 hours, and 6 hours, or any value within the above range.
[0042] According to an embodiment of the present invention, the sintered powder is crushed to a D50 of 0.65 μm-0.75 μm. Exemplarily, the sintered powder is crushed to a D50 of 0.65 μm, 0.66 μm, 0.67 μm, 0.68 μm, 0.69 μm, 0.70 μm, 0.71 μm, 0.72 μm, 0.73 μm, 0.74 μm, 0.75 μm or any value satisfying the above range.
[0043] In the present invention, the above step S4 may further include at least one of the following technical features:
[0044] According to an embodiment of the present invention, the pulse sintering is performed under a protective atmosphere.
[0045] According to an embodiment of the present invention, the pulse sintering is performed in a nitrogen atmosphere or an argon atmosphere.
[0046] According to an embodiment of the present invention, the pulse sintering temperature is 700° C.-750° C. Exemplarily, the pulse sintering temperature is one of 700° C., 710° C., 720° C., 730° C., 740° C., 750° C. or any value within the above range.
[0047] According to an embodiment of the present invention, the pulse sintering time is 1 hour to 2 hours. Exemplarily, the pulse sintering time is one of 1 hour, 1.5 hours, 2 hours or any value within the above range.
[0048] According to an embodiment of the present invention, the method further includes subjecting the pulse sintered material to air flow crushing, demagnetization and screening to obtain a high-valent element-modified LiFePO4 material.
[0049] According to an embodiment of the present invention, the pulse sintered material is air-grinded to a D50 of 0.90 μm-1.0 μm. Exemplarily, the D50 of the material is 0.9 μm, 0.95 μm, 1.0 μm or any value within the above range.
[0050] In the present invention, pulse sintering is adopted because such rapid sintering helps to maintain the structure of the material and prevent abnormal growth of grains, thereby obtaining a uniform, high-density, and densified sintered body.
[0051] In a second aspect, the present invention provides a high-valent element-modified lithium iron phosphate, wherein the high-valent element-modified lithium iron phosphate is prepared by the method described in the first aspect.
[0052] In a third aspect, the present invention provides an application of high-valent element-modified lithium iron phosphate in a lithium battery, wherein the high-valent element-modified lithium iron phosphate is prepared by the method described in the first aspect.
[0053] Compared with the existing technology, the introduction of high-valent elements as additives in the preparation process can adjust the primary particles to form a relatively uniform orientation microstructure due to their unique properties and eliminate the localized Li + The high-valent element reacts with lithium to form a lithium-containing ion conductor coating, which promotes the + It can also play a role in lithium supplementation during the cycle process, prevent the electrolyte from penetrating into the lithium iron phosphate material modified by the high-valent element, inhibit the interface side reaction, and realize the coordinated stability of the bulk phase and surface structure of the lithium iron phosphate material modified by the high-valent element; the combination of organic lithium salt and eutectic salt can not only avoid sintering at a high temperature, but also have good fluidity in the molten state, and can fully contact with iron phosphate. At the same time, the organic lithium salt of the present invention has rich functional groups, which can simultaneously realize the reduction of the iron valence state and the carbon layer coating; pulse sintering is adopted, because such rapid sintering helps to maintain the structure of the material and prevent abnormal grain growth, thereby obtaining a uniform, high-density and densified sintered body. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a TEM image of the high-valent element-modified lithium iron phosphate prepared in Example 1 of the present invention;
[0055] Figure 2 This is a TEM image of lithium iron phosphate prepared in Comparative Example 4 of the present invention;
[0056] Figure 3 The discharge capacity in grams of the embodiments of the present invention and the comparative example at different discharge rates;
[0057] Figure 4 The discharge capacity in grams of the embodiments of the present invention and the comparative example after 500 cycles at a 5C rate. DETAILED DESCRIPTION
[0058] The embodiments of the present invention are described in detail below. Unless otherwise specified, all scientific and technological terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present invention belongs. All patents and publications to which the present invention relates are incorporated herein by reference in their entirety. The term "comprising" or "including" is an open expression, i.e., including the contents specified in the present invention, but does not exclude the contents of other aspects.
[0059] According to the embodiment provided by the present invention, the present invention particularly provides a method for preparing lithium iron phosphate modified by a high-valent element, comprising the following steps:
[0060] S1: According to the molar ratio of Li:Fe element of 1:1.01-1.03, iron phosphate, lithium source (the molar ratio of organic lithium salt and eutectic lithium salt is 2-5:1), dispersant (the amount of dispersant added is 1.5%-1.6% of the mass of iron phosphate), additive (the molar ratio of additive to Fe is 0.01-0.02:1, and the molar ratio of high-valent element organic matter to high-valent element inorganic matter is 5-7:1), and water are mixed to obtain slurry Y with a solid content of 30%-32%;
[0061] S2: grinding the slurry Y to a D50 of 0.3 μm-0.35 μm, and then spray drying;
[0062] S3: Under a protective atmosphere, the powder collected after spray drying in step S2 is sintered at 400°C-500°C for 4h-6h, and the sintered powder is crushed to a D50 of 0.65μm-0.75μm;
[0063] S4: Under a protective atmosphere, the powder collected after crushing in step S3 is pulse sintered at 700°C-750°C for 1h-2h, air flow crushed, demagnetized, and sieved to obtain LiFePO4 material modified with high-valent elements.
[0064] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, if no specific conditions are specified, the conditions described in the specification or the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0065] Example 1
[0066] A method for preparing a high-valent element modified lithium iron phosphate material comprises the following steps:
[0067] S1: According to the molar ratio of Li:Fe element of 1:1.03, iron phosphate, lithium citrate and 0.3LiOH-0.2LiNO3 (the molar ratio of lithium citrate and 0.3LiOH-0.2LiNO3 is 2:1), oxalic acid, tantalum ethoxide and tantalum fluoride (the molar ratio of tantalum ethoxide and tantalum fluoride is 6:1), and water are mixed, the amount of oxalic acid added is 1.5% of the mass of iron phosphate, the molar ratio of the additive to the Fe element is 0.01:1, and a slurry Y with a solid content of 30% is obtained.
[0068] S2: The slurry Y was ground to a D50 of 0.3 μm and then spray-dried.
[0069] S3: Under a nitrogen atmosphere, the powder collected after spray drying in step S2 was sintered at 450° C. for 4 h, and the sintered powder was crushed to a D50 of 0.70 μm.
[0070] S4: In a nitrogen atmosphere, the powder collected after the crushing in step S3 is pulse sintered at 730°C for 1.5h, and the pulse sintered material is air flow crushed to a D50 of 0.95μm, demagnetized, and sieved to obtain a tantalum-modified lithium iron phosphate material.
[0071] Example 2
[0072] The only difference between this embodiment and embodiment 1 is that in step S1, the molar ratio of the additive to the Fe element is 0.015:1.
[0073] Example 3
[0074] The only difference between this embodiment and embodiment 1 is that in step S1, the molar ratio of the additive to the Fe element is 0.02:1.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that:
[0077] In step S1, the additives are niobium pentoxide and niobium ethoxide (the molar ratio of niobium pentoxide to niobium ethoxide is 6:1);
[0078] In step S4, the pulse sintering temperature is 700°C.
[0079] Example 5
[0080] The difference between this embodiment and embodiment 1 is that:
[0081] In step S1, the additives are ammonium molybdate and molybdenum hexacarbonyl (the molar ratio of ammonium molybdate to molybdenum hexacarbonyl is 6:1);
[0082] In step S4, the pulse sintering temperature is 725°C.
[0083] Example 6
[0084] The difference between this embodiment and embodiment 1 is that:
[0085] In step S1, the additives are tungsten boride and tungsten isopropoxide (the molar ratio of tungsten boride to tungsten isopropoxide is 6:1);
[0086] In step S4, the pulse sintering temperature is 750°C.
[0087] Example 7
[0088] The difference between this embodiment and embodiment 1 is that:
[0089] In step S1, the lithium salt is 4,5-dicyano-2-(trifluoromethyl)imidazolium lithium and 0.37LiOH-0.63LiCl (the molar ratio of 4,5-dicyano-2-(trifluoromethyl)imidazolium lithium and 0.37LiOH-0.63LiCl is 3:1);
[0090] In step S4, the pulse sintering temperature is 730°C.
[0091] Comparative Example 1
[0092] The only difference between this comparative example and Example 1 is that in step S1, the molar ratio of the additive to the Fe element is 0.005:1.
[0093] Comparative Example 2
[0094] The only difference between this comparative example and Example 1 is that in step S1, the molar ratio of the additive to the Fe element is 0.025:1.
[0095] Comparative Example 3
[0096] The only difference between this comparative example and Example 1 is that in step S1, no eutectic lithium salt (0.3LiOH-0.2LiNO3) is added.
[0097] Comparative Example 4
[0098] The only difference between this comparative example and Example 1 is that no additive is used in step S1.
[0099] Performance Test:
[0100] The high-valent element-modified LiFePO4 materials obtained in the examples and comparative examples were respectively made into positive electrode sheets. The process is as follows: the active material, conductive agent (SP+KS-6), and binder (PVDF) are mixed in a mass ratio of 86:5:3:6, and then the slurry is evenly coated on aluminum foil, vacuumed at 110°C overnight, cut into small pieces, and then assembled in an argon glove box. The half-cell is used as the counter electrode and the Xinzhoubang LBC305-1 is used as the electrolyte. The assembly specification is a CR2016 button cell. The constant current charge and discharge mode is used for charging and discharging, and the test results are shown in Table 1:
[0101] Table 1: Comparison of test data of embodiments and comparative examples
[0102]
[0103] As can be seen from Table 1, in Examples 1-7, the initial discharge capacity of the battery can reach more than 160 mAh / g, and the first coulomb efficiency is more than 98%. As can be seen from Examples 1-7 and Comparative Examples 1-2, if the coating layer is too thick or too thin, the capacity of the prepared lithium iron phosphate material will be reduced, the first coulomb efficiency will be reduced, and the cycle stability of the prepared lithium iron phosphate material will be affected.
[0104] It can be seen from Examples 1-7 and Comparative Example 3 that under high compaction, since Examples 1-7 use eutectic lithium salts, they have good fluidity in a molten state and can fully contact with iron phosphate, resulting in good crystallinity of the sintered lithium iron phosphate material and improved electrochemical performance.
[0105] It can be seen from Examples 1-7 and Comparative Example 4 that the addition of high-valent elements significantly improves the electrochemical performance and compaction density of the prepared lithium iron phosphate. This is mainly due to the proper doping to adjust the primary particles to form a relatively uniform orientation microstructure and eliminate the localized Li + In addition, the high-valent element reacts with the lithium source to generate an ion conductor coating containing lithium, which promotes the + It can not only transport lithium but also replenish lithium during the cycle, prevent the electrolyte from penetrating into the lithium iron phosphate material modified with high-valent elements, inhibit the interface side reactions, and achieve the coordinated stability of the bulk and surface structure of the lithium iron phosphate material modified with high-valent elements.
[0106] Depend on Figure 1 , 2 It can be seen that the surface of the high-valent element-modified lithium iron phosphate prepared by the method of the present invention is coated with lithium tantalate, while the surface of the lithium iron phosphate prepared in Comparative Example 4 without using additives has no coating layer.
[0107] Depend on Figure 3 , 4It can be seen that the high-valent element-modified lithium iron phosphate prepared by the method of the present invention has excellent rate performance and cycle stability.
[0108] In the description of this specification, the description with reference to the terms "some embodiments", "other embodiments", "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0109] Although the embodiments and examples of the present invention have been shown and described above, it is to be understood that the above embodiments and examples are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments and examples within the scope of the present invention.
Claims
1. A method for preparing high-valent element-modified lithium iron phosphate, characterized in that: The following steps are involved: S1: mixing iron phosphate, lithium source, dispersant, additive and solvent to obtain slurry Y; S2: grinding the slurry Y and spray drying it; S3: sintering and crushing the powder collected after spray drying in step S2; S4: Pulse sintering the powder collected after crushing in step S3 to obtain LiFePO4 material modified by high-valent elements; wherein the lithium source includes organic lithium salt and eutectic lithium salt; and the additive includes organic matter of high-valent elements and inorganic matter of high-valent elements.
2. The preparation method according to claim 1, characterized in that: The organic lithium salt is selected from at least one of 8-hydroxyquinoline-lithium, dilithium carbamoyl phosphate, lithium 2-thioglycolate, lithium citrate, and 4,5-dicyano-2-(trifluoromethyl)imidazole lithium; the eutectic lithium salt is selected from at least one of 0.3LiOH-0.2LiNO3, 0.38LiOH-0.62LiNO3, 0.37LiOH-0.63LiCl, 0.74LiOH-0.26Li2CO3, 0.71LiNO3-0.29LiCl, and 0.55LiI-0.45LiOH; Preferably, the molar ratio of the organic lithium salt to the eutectic lithium salt is 2-5:
1.
3. The preparation method according to claim 1, characterized in that: The dispersant is selected from at least one of polyethylene glycol, polyvinyl alcohol, polyacrylamide and oxalic acid; Preferably, the dispersant is 1.5%-1.6% by mass of the iron phosphate.
4. The preparation method according to claim 1, characterized in that: The molar ratio of the additive to Fe is 0.01-0.02:1; Preferably, the high-valent element exists in a form selected from Ta 5+ , Nb 5+ 、Mo 6+ , W 6+ At least one of; Preferably, the organic substance of the high-valent element is selected from at least one of tantalum ethoxide, niobium ethoxide, molybdenum hexacarbonyl, and tungsten isopropoxide; Preferably, the inorganic substance of the high-valent element is selected from at least one of tantalum fluoride, niobium pentoxide, ammonium molybdate, and tungsten boride; Preferably, the molar ratio of the organic matter of the high-valent element to the inorganic matter of the high-valent element is 5-7:
1.
5. The preparation method according to claim 1, characterized in that: The solvent is water; Preferably, the solid content of the slurry Y is 30%-32%; Preferably, the molar ratio of Li:Fe elements in the slurry Y is 1:1.01-1.
03.
6. The preparation method according to claim 1, characterized in that: In step 2, the slurry Y is ground to a D50 of 0.3 μm-0.35 μm and then spray-dried.
7. The preparation method according to claim 1, characterized in that: In step S3, the sintering process is performed under a protective atmosphere; Preferably, the sintering process is carried out in a nitrogen atmosphere or an argon atmosphere; Preferably, the sintering temperature is 400°C-500°C; Preferably, the sintering time is 4h-6h; Preferably, the sintered powder is crushed to a D50 of 0.65 μm-0.75 μm.
8. The preparation method according to claim 1, characterized in that: In step S4, the pulse sintering is performed under a protective atmosphere; Preferably, the pulse sintering is performed in a nitrogen atmosphere or an argon atmosphere; The pulse sintering temperature is 700°C-750°C; Preferably, the pulse sintering time is 1 h-2 h.
9. A high-valent element-modified lithium iron phosphate, characterized in that: The high-valent element-modified lithium iron phosphate is prepared by the method according to any one of claims 1 to 8.
10. Application of high-valent element-modified lithium iron phosphate in lithium batteries, characterized in that: The high-valent element-modified lithium iron phosphate is prepared by the method according to any one of claims 1 to 8.